Pengaruh Metode Pembelajaran Problem Solving terhadap Hasil Belajar Matematika Kelas V Sekolah Dasar Negeri - Khuzaimah Al Adawiyah; Yayah Huliatunisa; Samsul Azhar (RC-INSTITUT, 2021)
This study aims to obtain empirical data on the Effect of Problem Solving Learning Methods on Mathematics Learning Outcomes for Grade V Elementary School. The formulations of this problem are: 1) Problem Solving Learning Methods in Grade V Elementary School, 2) Mathematics Learning Outcomes of Grade V Elementary School Students, 3) Is There Any Effect of Problem Solving Learning Methods on Mathematics Learning Outcomes for Grade V Elementary Schools. And the objectives of the research are: 1) Knowing the effect of using problem sloving learning methods on Mathematics subjects, students at Tanah Tinggi 7 Tangerang State Elementary School. 2) Knowing the use of problem solving learning methods can affect the learning outcomes of Mathematics The samples in this study were all students of class V B totaling 31 students. Methods of data collection using posttest and pretest. The data collected were analyzed by correlational descriptive techniques. product moment is 0.994 and r table at a significant level of 0,05% and n = 31 is = 0.355. it means that r count > r table, it means that there is an effect of Problem Solving Learning Method on Mathematics Learning Outcomes for Grade V Elementary School. The magnitude of the effect of Problem Solving Learning Methods on Mathematics Learning Outcomes for Grade V Elementary School is = 0.342 determined by the value of the influence of problem solving learning methods, through the regression equation = 28.75 + 0.342X.